Effect of the incorporation of cellulose nanocrystals into a microwave-polymerized denture base resin: Cellulose nanocrystals into a denture base resin - Santana, Thais de Sousa [UNESP] (2022)
The aim is to evaluate the mechanical, physical, and microbiological properties of a denture base resin (Onda-Cryl, microwave-polymerized), after the incorporation of cellulose nanocrystals (CNC). Mixtures of CNC and the resin are prepared at 0% (control group), 0.25%, 0.5%, 0.75% and 1% for the flexural strength (FS) and Vickers hardness (VH) tests. Due to the VH results, surface roughness (SR), surface free energy (SFE), and the single- and dual-species biofilm formation of Candida albicans and methicillin-susceptible Staphylococcus aureus (MSSA) for metabolic activity (XTT assay), antimicrobial activity (CFU mL−1) and confocal laser microscopy tests are performed for the groups 0% and 0.75% CNC. Data are statistically analyzed (α =.05). For FS, CNC at 0.25%, 0.5% and 0.75% are similar to the control. A significant increase of VH is observed at 0.75% and 1%. The 0.75% CNC group is similar to the control for the SFE and SR tests. There is no significant difference between control group and 0.75% CNC group for adhesion and biofilm formation of different microorganisms analyzed for XTT and CFU mL−1. These results are corroborated by confocal microscopy images. The incorporation of CNC at 0.75% into a microwave-polymerized denture base resin provides promising results regarding VH and does not influence the physical, mechanical, and microbiological properties evaluated. These results suggest that the addition of CNC in the resin does not display surface alterations capable of increasing adhesion or biofilm formation of C. albicans or S. aureus.